2007
DOI: 10.1007/s00125-007-0727-8
|View full text |Cite
|
Sign up to set email alerts
|

A 10-s sprint performed prior to moderate-intensity exercise prevents early post-exercise fall in glycaemia in individuals with type 1 diabetes

Abstract: Aims/hypothesis We investigated whether a 10-s maximal sprint effort performed immediately prior to moderateintensity exercise provides another means to counter the rapid fall in glycaemia associated with moderate-intensity exercise in individuals with type 1 diabetes. Materials and methods Seven complication-free type 1 diabetic males (21.6±3.6 years; mean±SD) with HbA 1c levels of 7.4±0.7% injected their normal morning insulin dose and ate their usual breakfast. When post-meal glycaemia fell to ∼11 mmol/l, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 10 publications
1
63
0
1
Order By: Relevance
“…Of the remaining 17 articles, we decided not to include another eight studies in our meta-analysis due to three reasons that were identified post hoc, namely: (1) in five studies [20][21][22][23][24], patients were supplied with rescue dextrose or carbohydrates, which meant that glucose profiles were artificially altered by these emergency interventions; (2) two studies [25,26] consisted of a single 10 s sprint at the beginning/end of a session and could not therefore be strictly considered to be either CONT or IHE; and (3) one study [27] did not provide any data about inter-subject variability (mean population profiles only were given). During the process of peer review for this report, journal reviewers identified one extra study that fulfilled our inclusion criteria: Yardley et al [28].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of the remaining 17 articles, we decided not to include another eight studies in our meta-analysis due to three reasons that were identified post hoc, namely: (1) in five studies [20][21][22][23][24], patients were supplied with rescue dextrose or carbohydrates, which meant that glucose profiles were artificially altered by these emergency interventions; (2) two studies [25,26] consisted of a single 10 s sprint at the beginning/end of a session and could not therefore be strictly considered to be either CONT or IHE; and (3) one study [27] did not provide any data about inter-subject variability (mean population profiles only were given). During the process of peer review for this report, journal reviewers identified one extra study that fulfilled our inclusion criteria: Yardley et al [28].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…IHE consists of repeated bouts of supramaximal efforts interrupting longer periods of low to moderate intensity activity. So far, a limited number of studies have investigated IHE in type 1 diabetes, generally reporting a glycaemiastabilising effect when compared with continuous moderate intensity exercise (CONT) [4][5][6][7][8][9][10][11]. However, exercise in the majority of these studies was of limited duration and data regarding longer IHE duration are scarce [7].…”
Section: Introductionmentioning
confidence: 99%
“…At approximately 15:00 hours, the participants performed a 10 s maximal sprint on a front-access cycle ergometer (Repco, Melbourne, VIC, Australia) as described previously [14,15]. They then rested in a seated position for the remainder of the 60 min recovery period.…”
Section: Methodsmentioning
confidence: 99%
“…Unless otherwise stated, all results are expressed as mean ± SEM. Our sample size was calculated based on published data on the effect of intense exercise on blood glucose levels, glucose Ra, glucose Rd and the levels of the glucoregulatory hormones [8][9][10][11][12][14][15][16]. This sample size was calculated with a power of 1−β=0.8 and statistical significance was set at p<0.05.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation